Two years' experience of using the Bravo wireless oesophageal pH monitoring system at a single UK tertiary centre. (6th December 2016) - Rao, Nagendra M.; Campbell, David I.; Rao, Prithviraj
Abstract: Aim: The Bravo wireless pH monitoring system enables oesophageal pH to be monitored in children intolerant to nasal catheters and records measurements over 48 hours. This study aimed to document the minimum child weight that enabled successful capsule placement and any associated complications. We also compared the diagnostic sensitivity of 48 hours versus 24 hours. Methods: We included 203 consecutive patients (122 male children) with clinically documented or suspected reflux symptoms. The age range was two years to 19 years, and the minimum weight was 9.29 kg. The pH capsule was deployed endoscopically under general anaesthetic. Recordings taken over 24 and 48 hours were compared to determine the frequency of differences and correlations in the reflux index and DeMeester scores. Results: Testing using the detached probe was successful in 190 children (93.6%) with weight as low as 9.29 kg, with no side effects, with failed deployment being the most frequent problem. Clinically different results in the reflux index were found in 16% of the children's day 1 or day 2 readings (p < 0.0001), suggesting the benefit of 48‐hour measurements. Conclusion: Measuring oesophageal pH with the Bravo wireless pH monitoring system was successful in 93.6% of cases. A 48‐hour test improved the detection rate of gastro‐oesophageal reflux disease by 16%.